ANALISIS KEPRIBADIAN TOKOH UTAMA DALAM NOVEL GENDUK KARYA SUNDARI MARDJUKI (KAJIAN PSIKOLOGI SASTRA) - Nazilatul Masruroh (EDU-KATA, 2021)
This research was conducted with the aim of describing the main character's personality in the novel "Genduk" by Sundari Mardjuki (Literature Psychology Study) by using Abraham Maslow's perspective. The data in this study are derived from the novel Genduk by Sundari Mardjuki, Cetakan November 2017, the publisher of PT Gramedia Pustaka Utama, with a total of 232 pages. Data is collected by library method, see, record, and documentation. The findings of the study show that all the needs theory proposed by Abraham Maslow has been obtained by the main character. The five needs raised include physiological needs or basic needs, the need for security, needs to be owned and loved, the need for self-esteem, and the need for self-actualization. The results showed that the fulfillment of these five needs in the main character found a good personality development from the main characters, including sociability, compassion, helping, not being easily offended, never giving up in achieving desires, and wise in responding to conflicts or problems.